WHAT DRIVES ENTREPRENEURIAL RESILIENCE IN BATIK SMES? - R. Andro Zylio Nugraha; Agatha Saputri; Caesar Rosyad Achmadi; Muhammad Harfiansyah Makarim; Arief Nurrahman (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Small and medium-sized enterprises (SMEs), particularly those operating in cultural industries, often face significant challenges due to market uncertainty, technological change, and increasing competition. These conditions highlight the importance of entrepreneurial resilience in ensuring business sustainability. This study aims to examine the factors that drive entrepreneurial resilience among batik SMEs by analyzing the roles of innovation, cultural identity, and market adaptability. The study employs a quantitative research approach using survey data collected from batik SME owners in Yogyakarta, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that innovation, cultural identity, and market adaptability all have positive and significant effects on entrepreneurial resilience, with market adaptability showing the strongest influence. These findings suggest that strategic capabilities embedded in SMEs serve as important intangible resources that strengthen business resilience. The study contributes to the entrepreneurship literature by extending the Resource-Based View in the context of cultural-based SMEs.